2013
DOI: 10.1088/0004-637x/778/1/19
|View full text |Cite
|
Sign up to set email alerts
|

Comet 17p/Holmes: Contrast in Activity Between Before and After the 2007 Outburst

Abstract: A Jupiter-family comet, 17P/Holmes, underwent outbursts in 1892 and 2007. In particular, the 2007 outburst is known as the greatest outburst over the past century. However, little is known about the activity before the outburst because it was unpredicted. In addition, the time evolution of the nuclear physical status has not been systematically studied. Here we study the activity of 17P/Holmes before and after the 2007 outburst through optical and mid-infrared observations. We found that the nucleus highly dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…For example, the analysis of size and age of the particles in the dust trail of main belt object P/2012 F5 (Gibbs) in Stevenson et al (2012) was confirmed by Moreno et al (2012). The analysis of short-period comet 17P/Holmes in Stevenson et al (2014) is consistent with results obtained by several other groups including Reach et al (2010) and Ishiguro et al (2013). The analysis of the dust trail of 67P/Churyumov-Gerasimenko in Bauer et al (2012) is consistent with the large particles that have been found by the Rosetta mission (Rotundi et al 2015), providing further "ground truth" to our modeling techniques.…”
Section: Effect Of Initial Particle Velocity and Justification For Tsupporting
confidence: 88%
“…For example, the analysis of size and age of the particles in the dust trail of main belt object P/2012 F5 (Gibbs) in Stevenson et al (2012) was confirmed by Moreno et al (2012). The analysis of short-period comet 17P/Holmes in Stevenson et al (2014) is consistent with results obtained by several other groups including Reach et al (2010) and Ishiguro et al (2013). The analysis of the dust trail of 67P/Churyumov-Gerasimenko in Bauer et al (2012) is consistent with the large particles that have been found by the Rosetta mission (Rotundi et al 2015), providing further "ground truth" to our modeling techniques.…”
Section: Effect Of Initial Particle Velocity and Justification For Tsupporting
confidence: 88%
“…Another outburst, in 2007, was well observed, revealing a spherical envelope, a detached blob, and a central coma (see, e.g., Watanabe et al 2009;Reach et al 2010). Total ejecta mass was estimated to be (1 ∼ 610) × 10 10 kg (Altenhoff et al 2009;Reach et al 2010;Ishiguro et al 2010;Li et al 2011;Boissier et al 2012;Ishiguro et al 2013). The expansion speed on the plane of the sky of the dust envelope particles was 554 ± 5 m s −1 (Lin et al 2009;Montalto et al 2008).…”
Section: Comparison With Other Cometsmentioning
confidence: 96%
“…We applied a three-dimensional analysis to match the observed images, following the model in Ishiguro et al (2007), Hanayama et al (2012), and Ishiguro et al (2013). We adopted a power-law function for the terminal speed of ejected dust particles:…”
Section: Dust Dynamical Modelmentioning
confidence: 99%
“…To derive the ejection speed, mass, and kinetic energy of the dust cloud in a comprehensive manner, we conducted a model simulation to reproduce the observed morphologies of dust ejecta from the second outburst by following the scheme in Ishiguro et al (2013). The morphologies of dust clouds are generally determined by the ejection speeds and the effects of solar radiation pressure, which can be approximately given by a function of grain size.…”
Section: Ejecta Dynamical Modelmentioning
confidence: 99%